EVALUATION OF INVITRO ANTI DIABETIC ACTIVITY OF SEENDHIL HERBAL FORMULATION - T.G.NITHYA; M.Divagar; L.Juliet (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The main aim of the study was to screen the ethanolic extract of seendhil polyherbal formulation for its invitro antidiabetic activity and its efficacy in inhibiting alpha amylase and alpha glucosidase enzymes as inhibition of these enzymes prevents raise in postprandial glucose level in blood. Methods: Both solvent and aqueous extract were prepared and assayed for the presence of phytochemicals. In vitro α-amylase and α-glucosidase inhibitory activity of the formulation were determined according to standard method using acarbose as control.The pre substrate and post substrate addition absorbance was measured at 405 nm on a microplate reader. The increase in absorbance on substrate addition was obtained. Each test was performed three times and the mean absorption was used to calculate percentage enzyme inhibition. Results: The preliminary phytochemical screening of both aqueous and ethanolic extract showed the presence of significant secondary metabolites.Inhibition percentage of alpha amylase was 75.3percent with a IC50 value of 2.90mg/ml and for alpha glucosidase inhibition percentage was 79.8percent with a IC50 value of 2.78mg/ml. Conclusion :At the concentration of 10mg/ml the extract showed significant and higher inhibitory activity against α-amylase and α-glucosidase enzymes.The present study indicated that Seendhil formulation could be useful in management of postprandial hyperglycemia. Key words: Diabetes mellitus, hyperglycemia, alpha amylase, glucosidase, inhibition, Seendhil formulation.